Age Related Multiple Sclerosis Severity Score: Disability ranked by age. (December 2017) - Manouchehrinia, Ali; Westerlind, Helga; Kingwell, Elaine; Zhu, Feng; Carruthers, Robert; Ramanujam, Ryan; Ban, Maria; Glaser, Anna; Sawcer, Stephen; Tremlett, Helen; Hillert, Jan
Background: The Multiple Sclerosis Severity Score (MSSS) is obtained by normalising the Expanded Disability Status Scale (EDSS) score for disease duration and has been a valuable tool in cross-sectional studies. Objective: To assess whether use of age rather than the inherently ambiguous disease duration was a feasible approach. Method: We pooled disability data from three population-based cohorts and developed an Age Related Multiple Sclerosis Severity (ARMSS) score by ranking EDSS scores based on the patient's age at the time of assessment. We established the power to detect a difference between groups afforded by the ARMSS score and assessed its relative consistency over time. Results: The study population included 26058 patients from Sweden ( n  = 11846), Canada ( n  = 6179) and the United Kingdom ( n  = 8033). There was a moderate correlation between EDSS and disease duration ( r  = 0.46, 95% confidence interval (CI): 0.45–0.47) and between EDSS and age ( r  = 0.44, 95% CI: 0.43–0.45). The ARMSS scores showed comparable power to detect disability differences between groups to the updated and original MSSS. Conclusion: Since age is typically unbiased and readily obtained, and the ARMSS and MSSS were comparable, the ARMSS may provide a more versatile tool and could minimise study biases and loss of statistical power caused by inaccurate or missing onset dates.